Antibacterial Effectiveness of A Combination of Binahong (Anredera cordifolia) and Soursop (Annona muricata) Leaf Extract on The Growth of Escherichia coli in Vitro - Wiranty, Agna Shailla Monica; Arjita, I Putu Dedy; Setyowati, Ety Retno (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The high incidence of diarrhea and the increasing resistance of Escherichia coli to various first-line antibiotics has prompted the search for safer and more effective antibacterial alternatives. Herbal plants such as binahong leaves and soursop leaves are known to contain secondary metabolites with antibacterial potential. This study aims to determine the antibacterial effectiveness of a combination of binahong and soursop leaf extracts on the growth of Escherichia coli in vitro and to determine the most effective combination concentration. This study was a laboratory experimental study with a true experimental design, then tested against Escherichia coli using the agar diffusion method. Statistical analysis was performed using the Kruskal–Wallis test and continued with the Mann–Whitney test. The results showed that the combination of binahong and soursop leaf extracts was able to inhibit the growth of Escherichia coli at all concentrations tested. There was a statistically significant difference in the diameter of the inhibition zone between treatment groups (p < 0.05). The combination of extracts at a concentration of 50% showed more optimal inhibitory activity than other concentrations, which is thought to be influenced by the interaction of the active compounds in both extracts. In conclusion, the combination of binahong and soursop leaf extracts has antibacterial effectiveness against the growth of Escherichia coli in vitro and has the potential to be developed as a natural antibacterial alternative.